The expression and clinical significance of miR-1226 in patients with periodontitis - Yimin Du; Yue-sun Qi; Hui Chen; Guorong Shen (BMC Oral Health, 2021)
Abstract Background miR-1226 has been reported to be dysregulated in periodontitis, implying its potential functional role, which needs to be validated. The purpose of this study was to assess the clinical significance of miR-1226 in periodontitis. Methods Gingival crevicular fluid samples were collected from 50 healthy volunteers and 72 periodontitis patients. The expression of miR-1226 in collected samples was detected by RT-qPCR. The concentrations of pro-inflammatory cytokines were analyzed by ELISA. The relationship of miR-1226 expression level with patients’ characteristics was evaluated by the χ2 test and the Pearson correlation test. Results It was found that miR-1226 was downregulated in the gingival crevicular fluid of periodontitis patients compared with healthy volunteers. The downregulation of miR-1226 was negatively correlated with the pocket depth, attachment loss, plaque index, bleeding index, and MMP-8 concentration of patients. miR-1226 showed high sensitivity and specificity to discriminate periodontitis patients from healthy volunteers. Additionally, periodontitis patients had a relatively high concentration of pro-inflammatory cytokines, which is correlated with miR-1226 expression negatively. Conclusions miR-1226 could be an indicator for the diagnosis of periodontitis and has the potential to predict the development and severity of periodontitis.